2015
DOI: 10.17140/semoj-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 6 Week Plyometric Training Program on Agility, Vertical Jump Height and Peak Torque Ratio of Indian Taekwondo Players

Abstract: CitationSingh A, Boyat AV, Sandhu JS. Effect of a 6 week plyometric training program on agility, vertical jump height and peak torque ratio of Indian Taekwondo Taekwondo demands for quick change in direction while keeping balance, strength, speed and body control through high level of lower limb strength, agility to improve performance. Methodology: 30 elite national level male Taekwondo players (mean age 22.0±1.6 years; mean Height, 174.4±4.4; mean mass 62.4±6.9 kg, training experience were 21±2.29 years, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 6 publications
2
16
0
1
Order By: Relevance
“…Asadi (2013) found that after six weeks of semiweekly in-season plyometric training, elite male basketball players from the experimental group significantly improved their Illinois agility test performance by 7% from 17.36 ± 0.48 seconds to 16.14 ± 0.5 seconds. A significant increase in the performance of Taekwondo athletes' agility, isokinetic strength, and vertical jumps was observed after six-weeks of plyometric training (Singh et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Asadi (2013) found that after six weeks of semiweekly in-season plyometric training, elite male basketball players from the experimental group significantly improved their Illinois agility test performance by 7% from 17.36 ± 0.48 seconds to 16.14 ± 0.5 seconds. A significant increase in the performance of Taekwondo athletes' agility, isokinetic strength, and vertical jumps was observed after six-weeks of plyometric training (Singh et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Previous research showed that plyometric training positively increased agility. Some of the studies are on other sports types (Miller et al 2006, Rameshkannana & Chittibabub 2014, Vaczi et al 2013, Asadi 2013, Lehnert et al 2013, Singh et al 2015 on different age groups (Asadi & Arazi 2012, Thomas et al 2009, Söhnlein et al, 2014. In volleyball, the studies usually investigate the effect of plyometric training on jumping (Voelzke et al, 2012, Stojanovic et al 2012, Vassil & Bazanovk, 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agility is a person's physical ability to change direction quickly direction or body parts without interference with a balance is indicated to maintain static and dynamic balance (Aksoy, 2019;Arabaci et al, 2010;Chaabene et al, 2018;Singh et al, 2015Singh et al, , 2017Tirtawirya, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Amrinder Singh (2015) [1] pointed out that plyometrics training is a stretch and contraction link which stretches the muscles first and activates the storage and release of the potential energy of the muscles,thus bringing a fast and powerful form of motion of centripetal contraction. According to Iain M. Fletcher, Amy C. Scarfe (2004), Doan (2006) [2][3][4], Mark Bull (2012) [5] and Michael T Schofield (2015) [6], plyometrics training plan can obviously improve the club speed and hitting distance of golfers.…”
Section: Introduction mentioning
confidence: 99%